Relationship between tolerance of ambiguity and family cohesion with academic engagement based on mediating role of academic resilience in female students - Maryam Mirsadegh; Farzaneh Hooman; Rezvan Homaei (Shahid Beheshti University of Medical Sciences, 2021)
Background: The orientation of academic resilience is towards positive processes of life and psychological empowerment of students, so, academic resilience is a significant factor affects the tolerance of ambiguity and family cohesion in students, resulting in increased academic engagement. This study designed to assess the relationship between tolerance of ambiguity and family cohesion with academic engagement based on mediating role of academic resilience in female students in Ahvaz city. Method: This was a descriptive correlation study accomplished by path analysis. The study population comprised second-grade high-school female students in Ahvaz city in 2020. Using simple random sampling 216 of which were selected as the participants. The data gathering instruments were: the Schoolwork Engagement Inventory, the Tolerance for Ambiguity Scale, the Family Cohesion Scale, and the Academic Resilience Inventory. Results: Results revealed a good fit for the modified model (CFI=1.00, IFI=1.00, RMSEA=0.001). The results indicated that there was a significant direct relationship between family cohesion and academic engagement (β=0.365, P=0.001), and between tolerance of ambiguity and academic resilience (β=0.274, P=0.001). Moreover, there was a positive relationship between family cohesion and academic resilience (β=0.369, P=0.001), and between academic resilience and academic engagement (β=0.328, P=0.001). The results of indirect path analysis indicated that academic resilience had a mediating role in the relationship between tolerance of ambiguity and family cohesion with academic engagement. Conclusion: The modified model had a good fitness, and is an important stage in recognizing the factors affecting the engagement and academic achievement of students.